Differences in Reading Skills by Ethnicity/Race for Texas High School Students: A Statewide, Multiyear Examination (Global Journal of Human-Social Science, 2017)
Analyzed in this study was the extent to which differences were present in the reading skills of Texas high school students as a function of ethnicity/race (i.e., Asian, White, Hispanic, and Black). Archival data were obtained from the Public Education Information Management System on all Texas high school students for the 2004-2005 through the 2011-2012 school years. Statistically significant differences were present in reading skills by student ethnicity/race in all 8 school years. For all analyses, average reading scores were lower for Black students than for Asian, White, and Hispanic students. Similarly, average reading scores were lower for Hispanic students than for Asian and White students. Results were mixed for White and Asian students. Implications for policy and for practice are discussed, along with suggestions for future research. Suggestions for future research and implications for policy and practice were made.
Keywords: critical -thinking skills; ethnicity/race; exit level; literacy; reading skills